Cattle behaviour : appearance of behaviour in wild and confinement - Shahhosseini, Yazdan (SLU/Dept. of Animal Nutrition and Management (until 231231), 2013)
The wild ancestor of cattle, the aurox, became exterminated approximately 400 years ago in 1627 and populations of feral cattle are not numerous. Therefore, they are mostly under management and surveillance of humans (Clutton-Brock, 1999). Thus, the knowledge of wild cattle behaviour is limited and the research in cattle behaviour is mostly carried out with semi-wild herds or animals in captivity. As understanding of cattle behaviour has a strong correlation with production, well-being and general management of cattle, this paper focuses on some important aspects of cattle behaviour both on pasture and in confinement. Furthermore, the knowledge of animal behaviour can help to reduce the frequency and intensity of abnormal and undesirable behaviours caused by management.